A Rare Case of Effusive-Constrictive Pericarditis Caused by Streptococcus agalactiae: Emergency Surgical Treatment - Annarita Iavazzo; Giovanni Battista Pinna; Maria Grazia Romeo; Emilio Mileo; Emanuele Pilato; Luigi Di Tommaso (Medicina, 2022)
A 70-year-old male patient was admitted to the emergency room in cardiac arrest. The patient was resuscitated and then referred to our cardiac surgery department, where he was diagnosed with suspected effusive constrictive pericarditis. A failed trial of TEE-guided pericardiocentesis led to the decision of surgical intervention. Sternotomy was performed and revealed pericardial thickening and very dense adhesions involving the pericardium and both pleurae, suggesting a neoplastic disease. An extensive pericardiectomy and bilateral pleural decortication were performed. After surgery, the patient improved significantly and was discharged from the intensive care unit 24 h later. Pericardial thickening, dense adhesions, the amount and color of pericardial fluid and the aspect of epicardial tissue increased our suspicion of neoplastic disease. Histological samples were sent to be analyzed immediately; a few days later, they were unexpectedly negative for any neoplastic disease but showed a group-B-hemolytic Streptococcus agalactiae infection, which causes pericarditis in extremely rare cases. Postoperatively, the patient, under intravenous antibiotic and anti-inflammatory therapy, remained asymptomatic and was discharged ten days after the surgery. At the three-month follow-up, transthoracic echocardiography showed a normal right and left ventricular function with no pericardial effusion.